Management of a giant carbuncle on the posterior trunk with excision and grafting - Akram, Muhammad Usman; Atique, Hafsa; Siddiqui, Saad; Haider, Sohaib; Raza, Ahmed; Arshad, Naveed (Journal of the Pakistan Medical Association, 2021)
Carbuncle is a painful subcutaneous mass of infected hair follicles with a purulent discharge. It has predisposition in conditions like diabetes, immune-compromised states, chronic skin diseases etc. The authors present a case of a 67 year old diabetic male with a giant carbuncle on his back. Due to its large size, systemic co-morbidity and increased risk of complications in surgical treatment, a multi-disciplinary team approach was employed. Both general and plastic surgery were involved, who performed excision and soft tissue coverage respectively. Aim of the surgical intervention methods, like wide excision and debridement, application of vacuum assisted wound closure (VAC) and skin grafting was to minimize the healing time and risk of development of post-operative infection. The patient was surgically managed and sent home in a good condition. Continuous....